1993
DOI: 10.1111/j.1469-8137.1993.tb03882.x
|View full text |Cite
|
Sign up to set email alerts
|

The deposition of atmospheric ammonia and its effects on plants

Abstract: SUMMARY Across Europe, total nitrogen deposition is increasing and, of this total, atmospheric ammonia can contribute up to 50–80%. Average deposition of ammonia in the UK is likely to be around 15–20 kg ha−1 yr−1, while in The Netherlands, which has some of the highest rates of deposition, this value is likely to be between 40 and 50 kg ha−1 yr−1. It is argued that because of the processes of assimilation and nitrification this ammonia is an acidifying pollutant. Ammonia taken up by plants is most likely to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
219
0
7

Year Published

1996
1996
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 361 publications
(229 citation statements)
references
References 139 publications
3
219
0
7
Order By: Relevance
“…The build-up of free NH 4 + in the plant tissues may not necessarily inhibit photosynthesis or growth on a short-term basis. The acid-base regulation in cells depends on intrinsic features of the plant's metabolism (Pearson & Stewart 1993).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The build-up of free NH 4 + in the plant tissues may not necessarily inhibit photosynthesis or growth on a short-term basis. The acid-base regulation in cells depends on intrinsic features of the plant's metabolism (Pearson & Stewart 1993).…”
Section: Resultsmentioning
confidence: 99%
“…It is possible that throughfall is rich in NH 4 + as it was observed in forests in the polluted regions of The Netherlands, with concentrations of 0.32 to 2.4 mM (Van Breemen et al 1982). In several European countries, it was observed that 50% of the N compounds released into the environment consisted of NH 3 /NH 4 + , and this indicates the importance of these compounds for vegetation (Pearson & Stewart 1993). Besides being released from the soil, NH 3 can be emitted from senescing plant parts (Hanstein & Felle 1999).…”
Section: Introductionmentioning
confidence: 99%
“…However when nutrients, particularly nitrogen, are in excess, the plant physiological and growth response are negatively affected. This is due to nitrogen toxicity, and in aquatic or marine systems additional algal overgrowth, which both lead to a higher demand of carbon skeletons, thus causing physiological imbalance, ultimately leading to mortality and collapse (Pearson and Stewart, 1993;Marschner, 1995; for seagrasses reviewed in: Touchette and Burkholder, 2000;Burkholder et al, 2007). Along this eutrophication trajectory, prior to collapse, increasing plant cover thus may coincide with increasing physiological imbalance, which likely diminishes plant recovery potential.…”
Section: Best Estimate For Seagrass Health and Resilience?mentioning
confidence: 99%
“…1 It can even be generally produced in natural processes in animals, human and plants. 2 Ammonia can irritates skin, eyes and respiratory tract of humans when the concentration reaches to a certain value (the safety threshold is ∼25 ppm in air). 3 It is also flammable at concentration of ca.…”
mentioning
confidence: 99%